Sodium selenite increases drought tolerance by promoting jasmonic acid biosynthesis in cucumber - Dan Wen; Yang Zheng; Yujuan Han; Jiping Song; Shengnan Sun; Ning Yang; Xiao Wang (Horticulture Advances, 2023)
Abstract Jasmonic acid (JA) is an important and widely distributed plant hormone. However, the molecular and physiological mechanism of JA in improving drought tolerance in response to sodium selenite is limited. This work was performed to investigate the effects of exogenous sodium selenite application in promoting drought tolerance of cucumber. The drought tolerance of cucumber seedlings is enhanced under the application of selenite, positively influencing shoot fresh weight and chlorophyll relative content and altering the chloroplast ultrastructure. The contents of JA and JA-isoleucine (JA-ILE) increased significantly in response to selenite application under drought conditions. Furthermore, the expression of JA biosynthesis and regulatory genes, namely, LOX (Lipoxygenase), AOC (allene oxide cyclase), AOS (allene oxide synthase), and MYC2 (the basic helix-loop-helix (bHLH) protein) was upregulated to greater levels when selenite was added in combination with drought treatment. This study provides methods to mitigate drought stress and valuable theoretical support for further understanding the plant response to drought signals.